Measurement and disclosure criteria for biological assets for Chilean and Peruvian companies - Hernández Pajares, Julio; Tolentino Monjorte, Hilda (Cuadernos de Administración, 2024)
This article examines how listed companies in Peru and Chile have applied the measurement and disclosure criteria for biological assets under IAS 41. Additionally, it seeks to determine the influence of variables such as country, type of audit firm, nature of the biological asset, investment in biological assets, company size, and profitability on these measurement criteria and disclosure levels. We used a quantitative approach, a descriptive-relational cross-sectional study on the 2021–2022 financial statements, and a content analysis of the annual reports and Chi-Square, one-factor ANOVA, and Pearson correlation tests to test our hypotheses. The findings demonstrate that neither the country, type of audit firm, nor the type of biological asset impacted the measurement model. The disclosure level primarily includes descriptions of biological assets, agricultural activities, and financial risks; it is higher for Chilean companies and those audited by the ‘Big Four’ audit firms. There was a significant correlation between investment in biological assets and profitability with the level of disclosure, which is higher for companies with substantial investments in biological assets that seek greater transparency with their investors and creditors in their investment decisions.